AKTIVITAS LARVA Culex sp TERHADAP EKSTRAK SERAI DAPUR (Cymbopogon citratus) DI KECAMATAN MAULAFA KOTA KUPANG - Ua, Agatha Sada; Almet, Julianty; Laut, Meity Marviana (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
Dengue hemorrhagic fever (DBD) is still a health problem in Kota Kupang.DBD controls have been continuously performed to reduce the population of Culex sp. However, the modern larvicide has caused an environmental problem, toxic to species non-target and found to be resistance. The present study aimed to investigate the larvicidal activity of Cymbopogon citratuson Culex sp. The extract of C. citratus was used for larvicidal activity at concentration of 0%; 0.2%; 0.4%; 0.6%; 0.8% and 1%. The mortality rate was calculated after 2, 4, 12 and 24 hours. The results showed that the mortality of larvae was 5.3% (0%); 45.3% (0.2%); 70.6% 0.4%; 96% (0.6%); 100% (0.8% and 1%). The present investigation suggests the possible use of C. citratus as an ideal ecofriendly, larvicidal agent for the control of Culex sp.